An optimization technique on ultrasonic and cutting parameters for drilling and deep drilling of nickel-based high-strength Inconel 738LC superalloy with deeper and higher hole quality - Baghlani, V.; Mehbudi, P.; Akbari, J.; Nezhad, E.Z.; Sarhan, A.A.D.; Hamouda, A.M.S. (Springer Verlag (Germany), 2016)
In this research work, an ultrasonic assisted drilling system is employed to apply both rotation and vibration to drill bits. The transducer horn transfers power very efficiently and changes tools effortlessly. The setup used to conduct drilling tests is Inconel 738LC with depth-to-diameter ratios from 2 to 10 by conventional drilling (CD), ultrasonic assisted drilling (UAD), and electro discharge drilling (EDD). The effects of ultrasonic vibration amplitude, spindle speed, and number of steps to drill each hole on machining force and surface roughness in UAD are investigated. The results demonstrate not only a significant improvement in tool life (by applying ultrasonic vibration to the drilling process) but also a 40 % reduction in thrust force compared to CD. The UAD technique seems more appropriate than the EDD method due to the ability to reduce machining process time by up to 90 %, improve cylindricity by roughly 50 %, increase hole dimension accuracy by up to 80 %, and reduce surface roughness by 52 %.